2003
DOI: 10.2337/diacare.26.11.3080
|View full text |Cite
|
Sign up to set email alerts
|

The Treat-to-Target Trial

Abstract: OBJECTIVE -To compare the abilities and associated hypoglycemia risks of insulin glargine and human NPH insulin added to oral therapy of type 2 diabetes to achieve 7% HbA 1c .RESEARCH DESIGN AND METHODS -In a randomized, open-label, parallel, 24-week multicenter trial, 756 overweight men and women with inadequate glycemic control (HbA 1c Ͼ7.5%) on one or two oral agents continued prestudy oral agents and received bedtime glargine or NPH once daily, titrated using a simple algorithm seeking a target fasting pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

63
1,050
15
64

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,403 publications
(1,192 citation statements)
references
References 29 publications
63
1,050
15
64
Order By: Relevance
“…A similar problem bedevilled a previously published exenatide comparison with insulin, in which a change of −1.1% from a baseline HbA 1c level of 8.3% was achieved with insulin glargine [3]; in the original treat-to-target study, Riddle and colleagues achieved a 45% greater reduction in HbA 1c , from 8.6% at baseline to 7.0% [4]. Similar or better results were achieved with insulin detemir [7].…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…A similar problem bedevilled a previously published exenatide comparison with insulin, in which a change of −1.1% from a baseline HbA 1c level of 8.3% was achieved with insulin glargine [3]; in the original treat-to-target study, Riddle and colleagues achieved a 45% greater reduction in HbA 1c , from 8.6% at baseline to 7.0% [4]. Similar or better results were achieved with insulin detemir [7].…”
mentioning
confidence: 79%
“…In this study, insulin dose adjustment was simply left to the investigator. It is not clear from the paper what intensity of follow-up, selfmonitoring, or dose adjustment to what target occurred, but at 52 weeks the premix insulin dose was only 24 U/day, well below doses used in recent studies [4][5][6][7][8], and below doses normally encountered in clinical practice. This appeared not to be the result of hypoglycaemia in this particular group of patients-the reported hypoglycaemia rate was as low with insulin as with the glucagon-like peptide-1 mimetic.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…The present prospective, 4‐week, single‐center, randomized, open‐label, parallel‐group, treat‐to‐target study14 was carried out to compare the efficacy and safety of IDegAsp or basal insulin in combination with OHA therapy.…”
Section: Methodsmentioning
confidence: 99%
“…The clinical trials showed that the use of basal insulin as an add‐on to OAD in patients with type 2 diabetes achieved 7% HbA1c, and approximately half of the patients experienced symptomatic hypoglycemia20, 21, 22, 23, 24. However, in real‐world practice, a retrospective USA study and two prospective studies in Ireland and Japan found that approximately just 20% of the patients taking basal insulin could achieve HbA1c <7% with a low rate of hypoglycemia16, 25, 26.…”
Section: Introductionmentioning
confidence: 99%